PRODUKSI DAN DEKOMPOSISI SERASAH DAUN MANGROVE Rhizophora stylosa DI DESA PULAU SEMBILAN KECAMATAN PANGKALAN SUSU KABUPATEN LANGKAT SUMATERA UTARA - Fina Fitriyani; Yunasfi Djayus; Desrita Desrita (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
Mangrove litter in the form of leaves, twigs, and other biomass, which fell into the foodsource of aquatic biota and nutrients that determine the productivity of marine fisheries. Objectiveof tudy was to determine the production rate of leaf litter and to measure the decomposition rate ofR. stylosa leaf litter. The study carried from March until May 2016 in Pulau Sembilan Village,Pangkalan Susu District, Langkat Regency, Sumatera Utara. Litter production determined by thelitter trap in each station mounted five container nets and decomposition rate determined by 18 bagsof litter bag each station with initial litter weight was 50 g. The highest production value found inthe station I was 70,24 g/m2/75days and the lowest R. stylosa leaf litter production value found inthe station II was 54,98 g/m2/75days. The highest R. stylosa leaf litter decomposition rate found at15thobservational day was 1,54 g/day with composition rate constant value (K) found in the StationI, II, III was 12,68, 10,76, and 10,46, respectively.Keywords: decomposition, mangrove litter, production, Rhizophora stylosa